Nadzwyczajne środki wsparcia jako prawna ochrona unijnego rynku rolnego - Lipińska, Izabela (Wydawnictwo Naukowe UAM, 2017)
This article deals with issues related to the use of extraordinary measures of supporting agriculture in selected EU agricultural sectors, and in particular the financial support for milk producers and pig breeders whose activity is most exposed to market fluctuations. The aim of the deliberations was to determine the direction of EU support and to provide its evaluation. It has been found that the legal solutions adopted at the EU level may in the long run contribute to the improvement of the situation on the agricultural market. It is noteworthy that the EU legislator notices the need for an increased capacity of agricultural producers to manage risk and crisis situations, and for adopting new instruments to support their gains and reduce potential risks.

L’articolo si propone di considerare l’impiego delle misure eccezionali di sostegno all’agricoltura in settori agricoli scelti dell’UE, in particolare l’aiuto finanziario concesso ai produttori agricoli che producono il latte e allevano i suini, la cui attività è soggetta alle fluttuazioni di mercato. L’articolo si prefigge di stabilire gli orientamenti per il sostegno previsto dal legislatore dell’UE e la sua valutazione. L’autrice sostiene che le soluzioni giuridiche adottate a livello dell’UE, vista la loro struttura, possano contribuire a migliorare la situazione del mercato agricolo sul lungo periodo. Il legislatore dell’UE riconosce la necessità sia di aumentare la capacità da parte degli agricoltori di gestire il rischio e le situazioni di crisi sia di definire nuovi strumenti atti a sostenere il reddito agricolo e a compensare potenziali danni in futuro.
Legal protection of EU agricultural market founded on extraordinary support measures
La tutela giuridica del mercato agricolo dell’UE sulla base delle misure eccezionali di sostegno